Mikrischyrum musicum, a new katydid species from montane rainforest in southern Ecuador with complex pure-tone calling song (Orthoptera: Tettigoniidae: Pseudophyllinae: Platyphyllini) - Braun, Holger (Zootaxa, 2021)
The katydid Mikrischyrum musicum sp. nov. is described as third species of the genus, along with the remarkable low-ultrasound musical calling song of the male. It is the first species of the genus with known females, which are considerably larger than males and lack the conspicuous white spots on the pronotum. Pure-tone songs among pseudophyllines and development of pronotum markings of Platyphyllini are briefly discussed.